Projecting the Supply and Demand for Certified Genetic Counselors: a Workforce Study. Issue 1 (20th October 2017) - Hoskovec, Jennifer M.; Bennett, R. L.; Carey, M. E.; DaVanzo, J. E.; Dougherty, M.; Hahn, S. E.; LeRoy, B. S.; O'Neal, S.; Richardson, J. G.; Wicklund, C. A.
Abstract: As of May 2017, there were 4242 Certified Genetic Counselors (CGC) (American Board of Genetic Counseling, Inc.2017 ) and 41 graduate‐level genetic counseling training programs (Accreditation Council for Genetic Counseling2017 ) in North America, and the demand for CGCs continues to increase. In the Fall of 2015 the Genetic Counselor Workforce Working Group, comprised of representatives from the American Board of Genetic Counseling (ABGC), the Accreditation Council for Genetic Counseling (ACGC), the Association of Genetic Counseling Program Directors (AGCPD), the American Society of Human Genetics (ASHG), and the National Society of Genetic Counselors (NSGC) commissioned a formal workforce study to project supply of and demand for CGCs through 2026. The data indicate a shortage of genetic counselors engaged in direct patient care. Assuming two scenarios for demand, supply is expected to reach equilibrium between 2024 and 2030. However, given the rate of growth in genetic counseling training programs in the six months since the study was completed, it is reasonable to expect that the number of new programs may be higher than anticipated by 2026. If true, and assuming that growth in programs is matched by equivalent growth in clinical training slots, the supply of CGCs in direct patient care would meet demand earlier than these models predict.